Wdowieństwo jako droga do doskonałości w Żywotach świętych Piotra Skargi - Puchalska-Dąbrowska, Bernadetta (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The aim of the article is to present widowhood as a way to attaining Christian perfection in Piotr Skarga’s Lives of the Saints. The work, addressed to all the representatives of the spheres of life in the 16th and 17th century Poland, includes selected role models of widows, e.g. St. Elizabeth of Hungary or St. Bridget of Sweden. The main components of the model under discussion are: intensive spiritual life, detachment from the world and its pleasures, avoiding further marriages, poverty and deeds of charity. In the construction of the perfect widow, Skarga follows the writings of St. Paul and the lives of the religious.